Efektivitas Pemberian Ekstrak Sarang Semut (Myrmecodia .sp) Terhadap Respon Antibody Avian Influenza Subtipe H5N1 - Ertika Fitri Lisnanti; Nur Fitriyah (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
AbstractAvian influenza is a kind of contagious disease which can spread not only to other poultry but also to the human (zoonosis). Avian influeza becomes world issue when the human can effect the death. Sarang Semut plant (Myrmecodia .sp) which has much anti-oxidant and imunostimulant can increase immunity. Imunostimulant will help and protect body cells well. The increasing of cellular immunity will help the cell attack the AI virus and increase the work of avian influenza vaccine. Therefore, this research is done to know the influence of sarang semut extract toward poultry’s anti-body of avian influenza H5N1.This research using experimental method. The design used is RAL factorial. Factor I: the addition of sarang semut extract amounted 5mgs/kgs BB, 10 mg/kg BB, 15 mg/kg BB and Factor II: the length of giving sarang semut extract, namely:  3 days, 5 days, and 7 days. The result of this research was analyzed using variance analysis (ANOVA) followed by BNT.The result of serology examination shows that in adding sarang semut extract showing the significant different in each experiment, but not showing the significant different in the time given. The more increasing of the anti-body titer average and more decreasing CV can give  the more optimal protection for H5N1 virus attack. The recomended result on this research average titer and CV is giving sarang semut extract by 10 mgs/kgs BB dosage.